THE APPLICATION OF KAHOOT! IN QUIZ AS A LEARNING MEDIA FOR ENGLISH LITERATURE SEMIOTIC MATERIAL FOR GAME-BASED TESTS - Fajar Maulana Hidayat; Anggreni Kaita Ana Wulang; Putu Chris Susanto; Neil Prajamukti Wardhana (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThis study aims to determine the benefits of Kahoot! in the application of learning through games, and how the responses obtained from Kahoot! games are applied in English literature. The method used in this study is convenience sampling. In this study, it includes 3 (three) steps, such as: (1) watching YouTube videos containing material about stylistics (2) filling in the Kahoot! (3) filled out a questionnaire about the experience of participating in the Kahoot! The results of this study show several Point results such as: (1) the display of the quiz questions are categorized in Attractive options with a percentage value> 50%. The usefulness of the quiz with Kahoot! Media was obtained by 93% of respondents from the Good category, (2) According to students Kahoot! Games tend to be more fun than boring with an average rating of 4.33 and with 83% of respondents stating that the game is fun, useful as much as 93%, attracts as much as 83% and only 10% of respondents say they experience obstacles when playing Kahoot! (3) Gamification in Learning, the results of the assessment of respondents’ perceptions with a differential semantic scale show that for gamification students are interesting with a value of 87% pleasure, and adding variations to the value and Gamification is suitable to be applied in 80% of language learning, in addition gamification is more fun 77%, and appropriate gamification is applied in general learning with a percentage of 67%.Keywords: gamification learning, Kahoot, semiotics